HISTOGRAMS OF PERIODS DISTRIBUTION AND MODE IDENTIFICATIONS OF RRc LYR STARS - Bezdenezhnyi, V. P. (Одеські астрономічні публікації, 2017)
On the base of GCVS (General Catalogue of Variable Stars) sampling (381 stars with the known periods) has been carried out the analysis of periods of RRc Lyr stars. It has been given an interpretation of the histogram of periods distribution of these stars. All the peaks in the histogram were identified as radial overtones and their harmonics. It was proposed a new classification of these variable stars according to their mode identifications. The comparisons with the distributions of periods of δ Sct and other pulsating stars are carried out.